2020
DOI: 10.20473/ijosh.v9i3.2020.328-337
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Symptoms of Computer Vision Syndrome and Visual Display Terminal Utilization

Abstract: Introduction: The increased use of computers in the era of technological advances had an impact on the eye health called Computer Vision Syndrome (CVS), a compound eye problem caused by computer use. Almost every job could not be separated from the use of computers. Based on data from World Health Organization (WHO) in 2014, the incidence of asthenopia (eye fatigue) ranged from 40% to 90%. This research aimed to determine the relationship between symptoms of Computer Vision Syndrome and Visual Display Terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…This finding is consistent with the results of other studies. 19,20,57,58 A possible suggestion for this finding could be the cumulative exposure nature of CVS symptoms rather than being an acute condition that could prime to severe eye problems. As a result, long years of using a device equals more accumulated stress on the eyes, which might intensify the risk of developing CVS.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of other studies. 19,20,57,58 A possible suggestion for this finding could be the cumulative exposure nature of CVS symptoms rather than being an acute condition that could prime to severe eye problems. As a result, long years of using a device equals more accumulated stress on the eyes, which might intensify the risk of developing CVS.…”
Section: Discussionmentioning
confidence: 99%
“…In his report, he also mentioned that Darmaliputra and Dharmadi reported that 79.6% of computer users who work at a distance of less than 50 cm experience computer syndrome. 2,14 Priyambada (2019) also stated that the highest risk factor for premature presbyopia is close viewing of 30.5%.…”
Section: Discussionmentioning
confidence: 99%
“…75% of the respondents who complained of computer syndrome came from the group with more than 10 years of service, while 25% came from less than 10 years of service ( p-value 0.002). 2 However, Table 8 shows the percentage of bivariate test results on the VDT service period variable with a p-value of 0.723 with OR of 1.200 and 95% CI 0.437-3.293. The p -value > 0.05 in this study indicates that VDT working age is not significantly related to the occurrence of premature presbyopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who conduct online lectures using smartphones tend to spend all their lecture hours looking at digital screens at a distance that is not optimal. The best viewing distance to the Visual Display Terminal (VDT) such as laptops and smartphones is 50-60 cm and the viewing distance is not optimal if <50 and >60 cm (Nadhiva and Mulyono, 2020).…”
Section: Journal Ofmentioning
confidence: 99%